Modeling the trend, persistence, and volatility of inflation in Pacific Alliance countries: an empirical application using a model with inflation bands - Rodríguez, Gabriel (2024)
This paper estimates and analyzes the dynamics of trend inflation, as well as the persistence and volatility of the inflation gap in the Pacific Alliance countries (Chile, Colombia, Mexico, and Peru). For this purpose, the econometric approach is based on methodologies proposed by Stock and Watson (2007) and Chan et al. (2013). Among these, the AR-Trend-Bound model considers the implications of inflation targeting in estimating the unobserved components of inflation. The results indicate that this model effectively allocates most of the permanent component to trend inflation. Additionally, a decreasing trend in inflation in the 1990s, stabilization in the first two decades of the 21st century, and a growing trend inflation following the onset of the COVID-19 pandemic are observed in all four countries. The low levels of inflation gap persistence prior to the pandemic reflect the effectiveness of central banks in maintaining inflation close to its trend level. Finally, the volatility of the inflation gap identifies the “Great Moderation” of inflation, with increases in volatility during the pandemic reaching levels similar to those estimated in the 1990s.